Copper‐Catalyzed Arylation of Nitrogen Heterocycles from Anilines under Ligand‐Free Conditions. Issue 45 (3rd October 2014) - Toummini, Dounia; Tlili, Anis; Bergès, Julien; Ouazzani, Fouad; Taillefer, Marc
Abstract The arylation of pyrazole and derivatives can be achieved by coupling arenediazonium species (formed in situ from anilines) by using a catalytic system that employs low‐toxicity and inexpensive copper metal under very mild and ligand‐free conditions (T=20 °C). From other nitrogen heterocycles, the presence of an additive (NBu4I) significantly improves the efficiency of the catalytic system. These results represent the first examples of CN bond formation from arenediazonium species.